Building Social Capital Online During the COVID-19 Transition in Indonesia - Tawakkal Baharuddin; Sjafri Sairin; Achmad Nurmandi; Zuly Qodir; Hasse Jubba (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
The COVID-19 pandemic  not only causes health problems but also affects the level of social trust. Low social trust occurs in the public sphere and transforms in the digital space. This situation was then deemed necessary to rebuild social capital. This study aims to prove that there are still opportunities in times of crisis  where social capital can be re-formed, depending  on how social networks initiate voluntary activism on social media. This study used a quantitative approach. Data were collected from Twitter using Ncapture.  The data including information on COVID-19 cases were later analysed using the Nvivo 12 Plus software.  This study found that there is a possibility and opportunity  that  low social trust caused by  the COVID-19 pandemic can still be restored in times of crisis, at least by utilizing social media as a social networking center. Social networks on Twitter slowly shape cooperative behavior and social trust, and influence collectivities in rebuilding social capital.